The lymph node pre-metastatic niche - Sleeman, Jonathan P. (Journal of molecular medicine, 2015)
Lymph node metastases occur frequently during the progression of many types of cancer, and their presence often reflects poor prognosis. The drainage of tumor-derived factors such as antigens, growth factors, cytokines, and exosomes through the lymphatic system to the regional lymph nodes plays an important role in the pre-metastatic conditioning of the microenvironment in lymph nodes, making them receptive and supportive metastatic niches for disseminating tumor cells. Modified immunological responses and remodeling of the vasculature are the most studied tumor-induced pre-metastatic changes in the lymph node microenvironment that promote metastasis, although other metastasis-relevant alterations are also starting to be studied. Here, I review our current understanding of the lymph node pre-metastatic niche, how tumors condition this niche, and the relevance of this conditioning for our understanding of the process of metastasis.